The adoption of Human Resource Information System (HRIS) and employees engagement: evidence from United Arab Emirates - Alaa Aldin A. Al Athmay; Kamel Fantazy; Rafat Alaa Aldin Abdul Rahim (Journal of the Academy of Business and Emerging Markets)
The purpose of this paper is to examine the relationships among Human Resource Information Systems (HRIS)—transactional, relational and transformational—and user satisfaction and intention to engage. It also investigates the mediating role of user satisfaction in the relationship between HRIS attributes and intention to engage. Data were collected through a survey questionnaire of various public organizations in the United Arab Emirates (UAE). Using confirmatory factor analysis (CFA) and structured equation modeling (SEM) methods, the results indicate that HRIS attributes positively influence user satisfaction and intention to engage. The paper’s originality and value come from its theoretical contribution to literature in the context of Middle East. The theoretical and practical implications of these findings are also discussed.